2021
DOI: 10.2147/ppa.s302275
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Readability of Medicine Information Materials: The Case of Tikur Anbessa Specialized Hospital – Mixed Approach

Abstract: Background: Patients are frequently provided with medicine information materials (MIMs). Rendering medicine information through written material is a reliable method. Readability is an important attribute of written material that can affect the reader's ability to comprehend. Patient's perception can also affect the comprehensibility of written MIMs. Objective: The objectives of the study were to assess the readability of medicine information in Tikur Anbessa Specialized Hospital (TASH); and assessing patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Informing patients about individualized medicines is largely the responsibility of health professionals [7,16] and is mostly considered in in-personal visit settings [17,18]. It has been reported that the provision of information regarding the disease and the medication helps the patient to control their behavior and has a positive impact on the treatment outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Informing patients about individualized medicines is largely the responsibility of health professionals [7,16] and is mostly considered in in-personal visit settings [17,18]. It has been reported that the provision of information regarding the disease and the medication helps the patient to control their behavior and has a positive impact on the treatment outcomes [19].…”
Section: Introductionmentioning
confidence: 99%